Diet affects reproductive development and microbiota composition in honey bees - Anjali Zumkhawala-Cook; Patrick Gallagher; Kasie Raymann (Animal Microbiome)
Abstract Background Gut microbes are important to the health and fitness of many animals. Many factors have been shown to affect gut microbial communities including diet, lifestyle, and age. Most animals have very complex physiologies, lifestyles, and microbiomes, making it virtually impossible to disentangle what factors have the largest impact on microbiota composition. Honeybees are an excellent model to study host-microbe interactions due to their relatively simple gut microbiota, experimental tractability, and eusociality. Worker honey bees have distinct gut microbiota from their queen mothers despite being close genetic relatives and living in the same environment. Queens and workers differ in numerous ways including development, physiology, pheromone production, diet, and behavior. In the prolonged absence of a queen or Queen Mandibular Pheromones (QMP), some but not all workers will develop ovaries and become “queen-like”. Using this inducible developmental change, we aimed to determine if diet and/or reproductive development impacts the gut microbiota of honey bee workers. Results Microbiota-depleted newly emerged workers were inoculated with a mixture of queen and worker gut homogenates and reared under four conditions varying in diet and pheromone exposure. Three weeks post-emergence, workers were evaluated for ovary development and their gut microbiota communities were characterized. The proportion of workers with developed ovaries was increased in the absence of QMP but also when fed a queen diet (royal jelly). Overall, we found that diet, rather than reproductive development or pheromone exposure, led to more “queen-like” microbiota in workers. However, we revealed that diet alone cannot explain the microbiota composition of workers. Conclusion The hypothesis that reproductive development explains microbiota differences between queens and workers was rejected. We found evidence that diet is one of the main drivers of differences between the gut microbial community compositions of queens and workers but cannot fully explain the distinct microbiota of queens. Thus, we predict that behavioral and other physiological differences dictate microbiota composition in workers and queens. Our findings not only contribute to our understanding of the factors affecting the honey bee microbiota, which is important for bee health, but also illustrate the versatility and benefits of utilizing honeybees as a model system to study host-microbe interactions.